HUBUNGAN POLA MAKAN DENGAN STATUS GIZI PADA ANAK USIA 3 – 5 TAHUN - Riamah Riamah; Dewi Erlita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Malnutrition can limit an individual's ability to reach his full potential. Conditions of hunger and malnutrition that occur, can result in lack of energy to do work, reduce the ability to go to school, and decrease the power of concentration and the ability to learn. The purpose of this study was to determine the relationship of eating patterns with nutritional status in children aged 3-5 years in the jalau river village, the working area of the Puskesmas Kampar Utara. This research was conducted in the sunagi jalau village, the working area of the North Kampar Health Center with 53 respondents. The research design used is Descriptive Correlation using a questionnaire sheet. The analysis used is the frequency distribution and chi square to analyze the relationship between variables. The results of this study concluded that there was a significant relationship between diet and nutritional status in children aged 3-5 years (p value = 0.002) and POR value of 7.633 (2,244 - 25,956). It is expected that health workers will be able to improve their health promotion programs especially on nutrition and diet.